Immune‐independent acquired resistance to PD‐L1 antibody initiated by PD‐L1 upregulation via PI3K/AKT signaling can be reversed by anlotinib - Yuan Gao; Yingfang Feng; Shaochuan Liu; Yan Zhang; Jing Wang; Tingting Qin; Peng Chen; Kai Li (Cancer Medicine, 2023)
Abstract Despite the benefit with cancer immunotherapies in clinical implication, immunotherapeutic resistance occurred in many patients and the mechanism remains unknown. Increasing evidence has revealed that cell‐intrinsic programmed cell death ligand 1 (PD‐L1) may play a non‐negotiable part in immunotherapeutic resistance. Our present study aimed to elucidate the immune‐independent acquired resistance mechanism to PD‐L1 antibody. We found elevated PD‐L1 expression induced by PD‐L1 antibodies in cancer cell and vascular endothelial cells (VECs) with substantially acquired resistance to PD‐L1 antibodies. Moreover, proliferation of resistant cells was accelerated and the apoptosis was reduced in the absence of immune compared with parental cells. Subsequently, we confirmed that the activation of the PI3K/AKT pathway is involved in the upregulation of PD‐L1 expression. Finally, we found that low dose of anlotinib downregulated PD‐L1 expression only in VECs via inhibiting the PI3K/AKT pathway; however, the same effect was not observed in cancer cells. To sum up, our findings revealed that upregulation of PD‐L1 via activation of the PI3K/AKT signal pathway may promote acquired resistance to PD‐L1 antibodies in an immune‐independent manner. Significance These findings provide new mechanisms of immunotherapeutic resistance and effective evidence of anlotinib combined with immunotherapy.